Healing experiences of women survivors of childhood sexual abuse: A conceptual framework - Lee Ping, N.C.; Sumari, M. (2010)
This qualitative study is aimed to explore and understand the healing experience of women survivors of childhood sexual abuse. It will engage with a descriptive study that uses a phenomenological approach to explore the experience of a woman survivor. The process of collecting data will involve in-depth interview sessions. This will continue with self-reflection writing by the participant and researcher. The outcome of this study will contribute into a two areas. The first area is aimed to create awareness and understanding among helping profession the essence of healing experience encountered by women survivors with the intention to enhance the quality of the clinical work. The second area is aimed to contribute to education training especially for the new generation of helping professions.